Educação alimentar e nutricional análise de abordagem no currículo de ciências para estudantes do 5º ano do ensino fundamental da rede municipal de Varre-Sai/RJ - Oliveira, Hélida Ercília Macêdo de (2024)
It is important to recognize that eating is a voluntary and conscious process, where individuals seek food to satisfy hunger. However, eating goes beyond meeting biological needs; it is a source of pleasure, socialization, and expression of culture. Eating behavior begins in childhood based on what is transmitted by family and supported by traditions, beliefs, and taboos passed down through generations. With the publication of Law No. 13,666 on May 16, 2018, Nutrition Education (EAN) became part of the school curriculum, categorized as a cross-cutting theme. EAN is a field of action in Food and Nutritional Security and Health Promotion, crucial for preventing and controlling food and nutrition-related issues. Nutritional education has emerged as a prominent strategy in health education activities, focusing on disseminating information about healthy eating practices through a pedagogical and educational approach aimed primarily at behavioral change. Considering the above, this research aimed to investigate how Nutrition Education is addressed in the science curriculum for 5th-grade classes at a Municipal School in Varre-Sai, RJ. The study was conducted at E.M. Primo José Sobreira, located in the town center. Initially, the research involved document analysis of the educational materials used by 5th-grade teachers and how "Nutrition Education" is approached in the Science curriculum, following the guidelines of the BNCC (2018). Subsequently, semi-structured audio-recorded interviews were conducted with research subjects to assess their knowledge of the topic and how it is addressed in the classroom. Analysis of the results showed that teachers follow BNCC guidelines for content application, considering proposals from the Teacher's Manual. During interviews, teachers indicated a lack of specific knowledge in this area but expressed interest in integrating the topic into their classrooms, fostering discussions about students' and society's eating habits and nutrition.